COMPARATIVE STUDY BETWEEN SEMICONTINOUS AND INTERRUPTED AORTIC VALVE REPLACEMENT REGARDING POST-OPERATIVE PERMANENT PEACEMAKER REQUIREMENT - Rafeek Fekry Barsoum; Ahmed Labib Dokhan; Mohamed Ahmed El-Hag Aly; Mena Shafik Takla; Ahmed Hatem Onsi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Aortic valve replacement (AVR) is a well-established, safe treatment that provides significant advantages to patients with valvular disease.Objectives: to compare the early results of the interrupted and the semicontinuous suture techniques in AVR especially permanent pacemaker (PPM) requirements.Methods: This prospective study was conducted on 120 patients who underwent AVR between January 2021 and June 2022. The patients were randomly divided into two groups: Group I: 60 patients for AVR using interrupted suture technique. Group II: 60 patients for AVR using semi-continuous suture technique.Results: In group I, the mean age was 58.50 ± 8.03 years with 40 patients (66.67%) were males. The mean body mass index was 27.26 ± 4.84 Kg/M2. The preoperative echo: mean LVESD was 4.44 ± 0.76 cm, the mean LVEDD was 5.89 ± 0.66 cm and the mean LVEF was 47.56 ± 8.12 %. While in group II, the mean age was 59.22 ± 7.05 years with 46 patients (76.67%) were males. The mean body mass index was 26.36 ± 4.14 Kg/M2. The preoperative echo: mean LVESD was 4.19 ± 0.71 cm, the mean LVEDD was 5.69 ± 0.57 cm and the mean LVEF was 45.92 ± 2.61 %.Conclusions: Semicontinuous suture technique showed significantly better results than interrupted suture technique regarding the mean cardiopulmonary bypass (CPB) time, mean cross clamp time, using of temporary pacemaker, ventilation time, ICU stay and mean total hospital stay.